G610(P) Retrospective analysis of neonatal deaths secondary to infections in England and Wales, 2013–2015. (25th October 2020) - Ahmed, L; Oligbu, GI; Ferraras, L; Ladhani, SN
Abstract : Purpose: To estimate the overall and infection related neonatal mortality rate and the pathogens responsible using electronic death registrations. What is already known on this topic The UK has one of the highest neonatal mortality rates among industrialised countries. Infections are associated with significant morbidity and mortality in neonates. Neonatal mortality rates have declined with advancements in neonatal care. Results: Total number of deaths secondary to infection per gestation. Early onset (<7 days), Late onset >7 days. 1 The most common pathogens responsible for neonatal mortality in each category. Gram positive: GBS (~10%), gram negative: E.Coli (~6%), viruses: HSV- 3%, Fungi: candida 1%. 1 Design: retrospective analysis of national electronic death registrations data Setting : England and Wales Patients: Neonates aged <28 days Main outcome measures: Overall and infection related mortality rate per 1, 000 live births in term, preterm (28 36 weeks) and extremely preterm (<28 weeks) neonates the contribution of infections and specific pathogens; comparison withmortality rates in 2003 05. Conclusion: Overall and infection related neonatal mortality rates have declined, but the contribution of infection and of specific pathogens has not changed. What this study adds Both the overall and infection related neonatal mortality rates have declined over the past decade. The contribution of infections and of specific pathogens to neonatal deaths has not changed. Group B Streptococcus remains the single most important pathogen associated with neonatal deaths. Reference: Office for National Statistics. Vital Statitistics Summary, England and Wales. Health Stat Q. 2009;43 :26.